STUDY OF ATTITUDES OF HUMAN RESOURCES DEPARTMENT (HRD) MANAGERS ON WORKERS WITH DISABILITIES IN STAR HOTELS IN THE NUSA DUA, BALI - Gusti Ngurah Widyatmaja (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study aims to describe the characteristics of workers with disabilities, participation patterns, and motivating and inhibiting factors for workers with disabilities who are employed at five-star hotels in Nusa Dua, Bali. According to this article structures, this research employs a qualitative methodology. This study collects data through observation, interviews, and reviewing the relevant literature and the findings are presented in a narrative manner in the discussion section. The results of this study indicate that the Human Resources departments of five-star hotels in the Nusa Dua area of Bali do not provide special treatment for disabled employees, beginning with hiring, selection, and compensation. However, they are typically assigned positions that do not require direct interaction with tourists. Furthermore, characteristics of workers with disabilities in the hotel industry in the Nusa Dua-Bali Tourism Area are still dominated by men of productive age with outsourcing status. Due to legal regulations and government incentives, five-star hotels in Denpasar City are open to employing people with disabilities. However, the degree of disability of people with disabilities, a lack of education, poverty, and family and community attitudes that continue to discriminate against people with disabilities are obstacles for workers with disabilities in the hotel industry.